2015
DOI: 10.1007/s00167-015-3686-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior shoulder instability with engaging Hill–Sachs defects: a comparison of arthroscopic Bankart repair with and without posterior capsulodesis

Abstract: Case-control study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
1
33
0
3
Order By: Relevance
“…The depth of the Hill-Sachs lesion was the only preoperative predictive parameter of failure of this series. One explanation would be related to non-healing of the capsulotenodesis into the Hill-Sachs lesion, leaving the Bankart repair alone to stabilise the shoulder [7,8,15,16]. According a biomechanical model of the capsulotenodesis fixation into a Hill-Sachs lesion, we have shown that a deep and narrow defect made the fixation more critical (see Appendix).…”
Section: Discussionmentioning
confidence: 97%
“…The depth of the Hill-Sachs lesion was the only preoperative predictive parameter of failure of this series. One explanation would be related to non-healing of the capsulotenodesis into the Hill-Sachs lesion, leaving the Bankart repair alone to stabilise the shoulder [7,8,15,16]. According a biomechanical model of the capsulotenodesis fixation into a Hill-Sachs lesion, we have shown that a deep and narrow defect made the fixation more critical (see Appendix).…”
Section: Discussionmentioning
confidence: 97%
“…These factors determine the risk for reinjury that is associated with an increase of the structural damage of both bony structures and soft tissues In nearly all cases of anterior dislocation, a disruption of the labrum takes place, the so-called Bankart lesion. In most cases of acute and recurrent dislocation, a posterolateral fracture of the head, known as Hill-Sachs lesion, is seen [4,[8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The ''engaging'' Hill-Sachs lesion refers to one that engages the rim of the glenoid when the shoulder is abducted and externally rotated. Engaging Hill-Sachs lesions lead to recurrent instability and a high rate of failure when treated with arthroscopic Bankart repair alone [4,[8][9][10][11][12][13][14][15]. Failure to address this humeral osseous defect during arthroscopic and open stabilization surgery for glenohumeral instability leads to an increased rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations